2018
DOI: 10.3892/ol.2018.8241
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LSINCT5 promotes ovarian cancer cell proliferation, migration and invasion by disrupting the CXCL12/CXCR4 signalling axis

Abstract: Long stress-induced noncoding transcript 5 (LSINCT5) is a member of the LSINCT family, members of which are expressed during stress-induced cell formation and have also been reported to promote cancer progression. In the present study, the association between LSINCT5 expression and clinical significance was investigated and the biological function of LSINCT5 in epithelial ovarian cancer (EOC) was explored. LSINCT5 expression was examined in EOC tissues by reverse transcription-quantitative polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…The expression of CXCR6 in epithelial ovarian cancer is significantly higher than that in normal ovarian and benign tissues. Studies have shown that the expression of CXCR6 is associated with lymph node metastasis [36], and the same conclusions have been obtained in cell experiments [45]. Ovarian cancer cell lines OVCAR-3 and SKOV-3 with high expression of CXCR6 have higher migration and invasion abilities.…”
Section: Discussionsupporting
confidence: 61%
“…The expression of CXCR6 in epithelial ovarian cancer is significantly higher than that in normal ovarian and benign tissues. Studies have shown that the expression of CXCR6 is associated with lymph node metastasis [36], and the same conclusions have been obtained in cell experiments [45]. Ovarian cancer cell lines OVCAR-3 and SKOV-3 with high expression of CXCR6 have higher migration and invasion abilities.…”
Section: Discussionsupporting
confidence: 61%
“… 19 As a newly discovered lncRNA in recent years, LSINCT5 is located on the human 5p15.33 chromosome. Previous research has shown that LSINCT5 affects the development and progression of colorectal carcinoma, ovarian cancer, 20 gastric cancer, 21 esophageal cancer, and chronic heart failure, 22 , 23 but there is relatively little research on OS at present. However, our study revealed that LSINCT5 was highly expressed in OS tissues and cell strains, and the 5-year survival of patients with high expression decreased, which was consistent with the study of He et al 12 However, the relevant mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Xu et al [16] also showed high LSINCT5 expression was associated with large tumor size, deep tumor invasion depth and advanced TNM stage in colorectal cancer patients. Long et al [18] demonstrated that ovarian cancer patients with high LSINCT5 expression tended to have advanced FIGO stage and lymph node metastasis. However, Mansoori et al [19] indicated there was no significant correlation between LSINCT5 expression and clinicopathological characteristics in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%